2022
DOI: 10.3390/sexes3010010
|View full text |Cite
|
Sign up to set email alerts
|

Do Pornography Use and Masturbation Frequency Play a Role in Delayed/Inhibited Ejaculation during Partnered Sex? A Comprehensive and Detailed Analysis

Abstract: The role of masturbation frequency and pornography use on sexual response during partnered sex has been controversial, the result of mixed and inconsistent findings. However, studies investigating this relationship have often suffered from methodological shortcomings. We investigated the role of masturbation frequency and pornography use on both the occurrence and severity of delayed/inhibited ejaculation (DE), an increasingly common sexual problem among men. We did so in a large (nonclinical) multinational sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…Specifically, anxiety and negative emotions—whether sex-specific or more general distress—received the strongest endorsements from respondents, a pattern consistent across both DE + ED and pure DE groups. The association between anxiety and sexual performance problems has long been known, 10 , 18 , 20 , 27 , 43 but we were surprised that it occupied such primacy in the list of reasons for DE symptomology: as noted in Table 5 , 4 of every 10 participants uniquely identified it as the most important typal reason for their problem. Whether or not anxiety/distress is an actual cause for the sexual difficulty is not known; however, whether cause or consequence, it was the reason most associated with difficulty reaching orgasm by the men in our sample and, as such, reiterates the importance of the management of stress/anxiety in any protocol designed to address this sexual problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, anxiety and negative emotions—whether sex-specific or more general distress—received the strongest endorsements from respondents, a pattern consistent across both DE + ED and pure DE groups. The association between anxiety and sexual performance problems has long been known, 10 , 18 , 20 , 27 , 43 but we were surprised that it occupied such primacy in the list of reasons for DE symptomology: as noted in Table 5 , 4 of every 10 participants uniquely identified it as the most important typal reason for their problem. Whether or not anxiety/distress is an actual cause for the sexual difficulty is not known; however, whether cause or consequence, it was the reason most associated with difficulty reaching orgasm by the men in our sample and, as such, reiterates the importance of the management of stress/anxiety in any protocol designed to address this sexual problem.…”
Section: Discussionmentioning
confidence: 99%
“…These reasons might also include a strong autoerotic orientation that—for whatever reason—lead some men to prefer the physical and psychological (eg, sexual fantasy) stimulation associated with masturbation over that of partnered sex. 18 , 20 On a positive note, both inadequate stimulation and low arousal are processes that could be addressed within the sexual dyad, particularly under the guidance of a knowledgeable therapist. 1 , 3 , 49 Specifically, relative to partnered sex, DE symptomology is greatly attenuated during masturbation 49 and, consistent with this general idea, the current study found that nearly 3 out of every 4 men who indicated difficult or absent ejaculation during partnered sex reported no or only mild difficulty during masturbation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations